8x-(5x+7)=4x-26

Simple and best practice solution for 8x-(5x+7)=4x-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-(5x+7)=4x-26 equation:


Simplifying
8x + -1(5x + 7) = 4x + -26

Reorder the terms:
8x + -1(7 + 5x) = 4x + -26
8x + (7 * -1 + 5x * -1) = 4x + -26
8x + (-7 + -5x) = 4x + -26

Reorder the terms:
-7 + 8x + -5x = 4x + -26

Combine like terms: 8x + -5x = 3x
-7 + 3x = 4x + -26

Reorder the terms:
-7 + 3x = -26 + 4x

Solving
-7 + 3x = -26 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-7 + 3x + -4x = -26 + 4x + -4x

Combine like terms: 3x + -4x = -1x
-7 + -1x = -26 + 4x + -4x

Combine like terms: 4x + -4x = 0
-7 + -1x = -26 + 0
-7 + -1x = -26

Add '7' to each side of the equation.
-7 + 7 + -1x = -26 + 7

Combine like terms: -7 + 7 = 0
0 + -1x = -26 + 7
-1x = -26 + 7

Combine like terms: -26 + 7 = -19
-1x = -19

Divide each side by '-1'.
x = 19

Simplifying
x = 19

See similar equations:

| -x/2=11-1/2 | | 4ln(2x+8)=28 | | c=10d+5n | | (2+3+4)/3 | | X^3+2x^2-5x-2=0 | | -(9x+1)= | | 4(w+4)=w-15 | | 8x-12=5x-9 | | 6c=39 | | 9y+3+11y+4= | | -x/2=111/2 | | 5/6y-2/3y=1/3 | | 24abc-24bac= | | 5.5j+4.2k= | | .8x+2=-.4 | | b+88=64 | | 3*(x-1)=6 | | -5(-8+3k)= | | 22=60+2 | | 8x+3-5x-9= | | 169/(12+1) | | 3g+4(-5+2g)=1-g | | 1+2x-x=x-5+5 | | -6(p-4)= | | -(-x+5)-8x=29-5x | | v=1/3*3.14r2 | | n-(11-2n)=16 | | 1/3(d-9)=-12 | | a-13=129 | | (m/4+n/3)(3m/4-2n/3)=0 | | 25x+15+0.5(x-4)=1.2x+2(0.9-6) | | -2(x-7)=-10 |

Equations solver categories